THE EFFECT OF SUITABILITY OF PROVIDING COMPLEMENTARY FOODS ON THE INSIDENCE OF STUNTING AND ANEMIA IN TODDLERS - Lailatul Khusnul Rizki; Esty Puji Rahayu (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: Stunting is a chronic nutritional problem in toddlers characterized by height that is not appropriate for their age. Children who are stunted will be at risk for disease and when growing up are at risk for degenerative diseases. The effect of stunting does not only affect health but also affects children's intelligence. Apart from stunting, anemia in children is also a health problem in developing countries (Ministry of Health, 2018).Objectives: The purpose of this study was to analyze the accuracy of giving complementary foods to the incidence of stunting and anemia in toddlers.Methods: The type of research used is analytical survey with a retrospective design. The population in this study are all toddlers at Porong Public Health Center who meet the inclusion criteria. The sample of this research is taken by cluster random sampling technique of 99 respondents. Data were collected using a questionnaire on complementary complementary feeding practices based on WHO (2003) regarding the principles of providing complementary foods. The reliability test of this questionnaire obtained a Cronbach’s Alpha value 0.723. Stunting Variables determined by calculating the Z-Score PB/U and Anemia variable was determined based on the measurement of the hb level Descriptive statistics and Chi-square Test with significance value less than 0.05 were used to analyzed data.Results: The results of this study are that there is an effect of the suitability of complementary feeding on the incidence of stunting and anemia, with a (ρ value = 0.001) for the variable incidence of stunting and (ρ value = 0.021) for the variable incidence of anemia.Conclusion: Socialization on complementary complementary foods must be carried out frequently to avoid stunting and anemia so that the government's target to reduce stunting can be achieved. Keywords: Complementary Foods, Stunting, Anemia, Toddlers